Theory of Planned Behavior as an Antecedent in Predicting Fraudulent Intentions of Academic Accountants and Non-Academic Accountants - Novi Lailiyul Wafiroh; Wuryaningsih Wuryaningsih (Jurnal Akuntansi Aktual, 2024)
Purpose: